Original papersEvaluation of morphological characteristics of septal rims affecting successful transcatheter atrial septal defect closure in children and adults - Oflaz, Mehmet Burhan; Pac, Feyza Aysenur; Kibar, Ayse Esin; Balli, Sevket; Ece, Ibrahim (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Introduction : Determining other echocardiographic predictors along with the measured atrial septal defect (ASD) size and evaluating the closure together with these predictors would increase the chance of success for transcatheter closure of ASD. Aim: To evaluate echocardiographic parameters affecting defect closure in children and adult patients with secundum ASD. Material and methods : In all patients, size of ASD, total length of atrial septum (TS), superior-posterior, inferior-posterior, superior-anterior and inferior-anterior rims surrounding the defect were measured by transesophageal echocardiography (TEE), and several measurement ratios were derived on the basis of TEE parameters. Results: A total 216 patients with secundum ASD were included in this study. The device was successfully implanted in 65 children and 65 adults. Both in pediatric and adult cases, the ratio of successful closure was found to be significantly higher when the ratio of defect size to TS was ≤ 0.35, the ratio of superior-anterior (SA) rim to the defect size was > 0.75 and the ratio of inferior-posterior (IP) rim to the defect size was > 1.0. It was found that having more than one of these predictors in a single case increased the chance of closure success significantly (p < 0.001). Conclusions : We concluded that a ratio of the defect size to TS ≤ 0.35, a ratio of SA rim to defect size > 0.75 and a ratio of IP rim to defect size > 1.0 were found to be echocardiographic predictors that could be used in successful transcatheter ASD closure both in children and adults.